Risk of manic switch with antidepressants use in patients with bipolar disorder in a Nigerian neuropsychiatric hospital (2018)
Background: Depressive disorders are common among those with bipolar affective disorder (BAD) and may necessitate the use of antidepressants. This has been suggested to precipitate manic episodes in some patients. Objectives: This study aims to determine the prevalence of and factors associated with manic switch in patients with BAD being treated with antidepressants. Methods: Case notes of patients who were treated at a Nigerian neuropsychiatric hospital for a BAD from 2004 to 2015 were reviewed. BAD diagnosis was made using ICD-10 criteria. Treatment for bipolar depression included monotherapy (i.e. antidepressants, antipsychotics or mood stabilisers) or combination therapy (mood stabiliser with an antidepressant or a combination of mood stabilisers, antipsychotics and antidepressants). The primary outcome measure was a switch to mania or hypomania within 12 weeks of commencing an antidepressant. Results: Manic or hypomanic switch (MS) was observed in 109 (44.3%) of the participants. Female gender, younger age, number of previous episodes and a past history of psychiatric hospitalisation were all significantly associated with a risk of MS. There was no significant difference in the rate of MS in either those treated with adjunct antidepressants therapy with a mood stabiliser or an antipsychotic or those placed on a combination of antidepressants, antipsychotics and mood-stabilising agents. Conclusion: A large proportion of patients with BAD on antidepressants experience medication-induced manic or hypomanic switch.